Financial and ethical integrity of judges - Malekh, Vitaliy Petrovych (Global Prosperity, 2025)
Abstract. The article highlights the issue of the financial and ethical criterion of the integrity of judges as a factor in the renewal of the judicial corps and the reform of the judiciary in Ukraine. It is stated that the institution of the integrity of the judicial system in democratic states has a primary role, since the latter is endowed with the potential of the highest judicial protection of human rights and public institutions of the state. Ukraine's democratic aspirations and the European integration direction of the development of social reality require the implementation of the principles of the rule of law, judicial independence and the integrity of the judiciary in modern Ukrainian politics. The author indicates that in the context of independence, the standard of integrity requires not only to foresee and ensure the absence of political, but also economic pressure. This includes an appropriate financial, economic and infrastructural base for the performance of their powers not only by judges, but also by other representatives of the judiciary, including decent remuneration for this category of employees. Such a requirement will ensure not only the functioning of the justice system, but also serves as a significant warning against manifestations of financial dishonesty, i.e., corrupt acts. It is positioned that the integrity of judges is of priority importance for reforming the judicial system and building a democratic society. The presence of clear organizational, legal and institutional means to guarantee integrity creates the basis for solving such urgent problems. It is stated that financial and ethical integrity are two main criteria for such an institution. The financial integrity of judges consists in the need to comply with anti-corruption legislation, eliminate and prevent conflicts of interest, and personal control over the financial sphere. We propose to understand ethical integrity as the internal qualities of a representative of the judicial corps, which ensure the performance of their official duties and the administration of justice in accordance with the principles of morality, justice, the rule of law, with compliance with high ethical standards that are characteristic of modern society and the representation of such behavior in extra-professional life.